Fatigue lifetime of AlBC3 alloy by ultrasonic fatigue testing machine in cavitation regime. Issue 13 (5th August 2015) - Cho, I.S.; Amanov, A.; Park, I.G.
Abstract : In this study, the influence of ultrasonic nanocrystalline surface modification (UNSM) technique on the cavitation fatigue properties of AlBC3 alloy was investigated. The fatigue properties of the untreated and treated specimens were assessed using an ultrasonic fatigue testing (UFT) machine. The treated specimens exhibited longer fatigue life in comparison with those of the untreated specimens, which may attributed to the plastically deformed layer at the top surface of the treated specimen. Also, a fracture analysis was studied using a scanning electron microscopy (SEM) to shed light on the fracture behavior of the specimens.